The Role of MicroRNAs in Myeloid Cells during Graft-versus-Host Disease - Chen, Sophia; Zeiser, Robert (Frontiers in Immunology, 2018)
The successful treatment of various hematologic diseases with allogeneic hematopoietic cell transplantation is often limited by the occurrence of graft versus host disease (GvHD). Several microRNAs have recently been shown to impact the biology of GvHD by regulating pro as well as anti inflammatory target genes. There is increasing evidence that a single microRNA can have different effects by preferentially targeting certain genes depending on the cell type that the microRNA is analyzed in. This review will focus on the role of microRNAs in myeloid cells during the development of acute and chronic GvHD. Because microRNAs act on the expression of multiple target genes and may thereby influence the immune system at different functional levels, they are potentially attractive targets for the modification of allogeneic immune responses using microRNA mimics and inhibitors.